Caracterização da anisotropia magnetocristalina de sistemas de nanopartículas de magnesioferrita a partir de espectros de ressonância - Santos, Ilza Tenório Cavalcante (2016)
In this work is described a study of the magnetic anisotropy of a magnesioferrite nanoparticle system (MgFe2O4) obtained by precipitation in solid solution of magnesiowüstite [Mg, Fe]O. The anisotropy field was obtained from system’s resonance spectra as measured in the X band. Such spectra can be considered as composed by two spectral lines: A broad line assigned to blocked particles at the measuring temperature and a thin line, which can be attributed to unlocked (superparamagnetic) particles. The anisotropy field of four samples treated at 700 °C during different annealing times were obtained from the spectra measured with their easy magnetization axes oriented at 0 ° and 45 ° with the applied field. The use of a theoretical model to adjust the obtained anisotropy field data enabled the obtaining of the model’s parameter values and their posterior comparison with those reported by other authors. Beyond the dependence of the anisotropy field with the measurement temperature and the sample’s treatment time, it was observed the presence of low field resonance lines that may be related to transitions usually considered as forbidden, which can be enabled by the degenerescence breaking caused by dipolar magnetic interactions between particles. Such phenomenon, which is considerably rare to observe in magnetic nanoparticles systems, was clearly observed in the studied system not only for the half-field resonance line (2Q), but also for lines appearing at one third of field (3Q) and at one quarter of field (4Q). This feature shows that, at least in the investigated experimental system, the dipolar interactions between nearby particles cannot always be neglected as has been proposed by several other authors.